Metaverse, implemented. A philosophical perspective on agenda-setting ethical tools for the development of immersive technologies - Tirinzoni, Mariachiara (Frontiers in Virtual Reality, 2025)
The specific application of immersive technologies known as metaverse emerges as a potential substitute for current social networks. Given the social and anthropological effects we have been able to observe as a consequence of the mass adoption of social networks, the following work aims to provide the initial sketch of a framework for structuring an approach to the design and deployment of the metaverse that safeguards the values of transparency, justice and fairness, avoiding simplistic but potentially distorting drifts already suggested by major actors. The reflection works on a definition of the metaverse as an object endowed by both the features of a space and the ones of a tool, exploring a shift of perspective that, drawing on the theory of affordances, sees an important role of ethical thinking not just in the design of the metaverse, but in its deployment and implementation too.